Actinomycin-D vs Methotrexate in Low-Risk Gestational Tropoblastic Neoplasia: Which is the better option? - Kaware, Heronimus Hansen; Wijaya Khoo, Kevin; Hapsari, Balivia Andi Permata (Indonesian Journal of Obstetrics and Gynecology, 2024)
Background Low-Risk Gestational Trophoblastic Neoplasia (LRGTN) is a malignant trophoblastic disease that can be cured with the proper management. Actinomycin-D (ACT) and Methotrexate (MTX) have been used as a single drug regimen for LRGTN. Therefore, this study aims to compare the efficacy and safety of ACT-based regimen and MTX-based regimen for LRGTN treatment. Methods Electronic databases were systematically searched for Randomized Controlled Trials (RCTs) and High-Quality Non-Randomized Controlled Trials (Non-RCTs) comparing ACT with MTX for patients with LRGTN. Studies were fully screened, extracted, and assessed. Studies without Complete Remission (CR) were excluded. The meta-analysis was carried out to quantify the efficacy and safety of each ACT and MTX regimens based on odds ratios (ORs) and 95% confidence intervals (95% CIs). Results: In total, 8 RCTs and 14 non-RCTs were included (2203 patients). Our study concludes that ACT has a higher CR than MTX (79.4% [716/902] vs 66.9%[871/1301]; OR 2.13; 95% CI 1.46-3.10, in the random-effects model). Furthermore, ACT is better in terms of efficacy compared to MTX in both the RCTs [81.2% (259/319) vs 66.1% (199/301); OR 2.17; 95% CI 1.49-3.16, in the fixed-effects model] and non-RCTs group [457/583 (78.4%) vs 672/1000(67.2%); OR 2.10; 95% CI 1.28-3.45, in the random-effects model]. Safety wise, the use of ACT has a higher incidence of alopecia (OR 3.52, 95% CI: 1.27-9.75, in the random-effects model) compared to MTX while MTX has a higher risk of developing liver toxicity (OR 0.54, 95% CI: 0.32-0.91, in the fixed-effects model) compared to ACT. Other side effects are not significantly different between the two groups. Conclusion: Our meta-analysis concluded that ACT has a better efficacy compared to MTX for LRGTN patients. In terms of safety, ACT-based regimens have a higher chance of suffering from alopecia and a lower chance of suffering from liver toxicity. Future clinical studies on single-drug regimens for LRGTN should be conducted in order to produce higher-quality data. Keywords: Methotrexate, MTX, Dactinomycin, Actinomycin-D, ACT, Low-Risk Gestational Trophoblastic Neoplasia, LRGTN